A STUDY ON STUDENTS’ ABILITY IN USING PICTURES ON READING DESCRIPTIVE TEXT AT 10th GRADE MA SABILAL MUHTADIN TEMBILAHAN - Febriana Anisa Putri; Agus Mustajib; Maizarah Maizarah (J-Shelves of Indragiri (JSI), 2019)
Reading is one of the four language skills that should be mastered by language learners. Through reading, they enable us to gain the information needed. Moreover, the purpose of this study is to investigate how the students' ability in using pictures on reading descriptive texts. The research design of this research was descriptive quantitative research. The population in this research was 10th grade of MA Sabilal Muhtadin Tembilahan, the population was group or cluster as classes. The sampling technique was a purposive sample. The students’ mean score was 63, it can be seen 6 students in interval 81-100 with category is very good, or with presentation (15%), 16 students in interval 61-80 with category is good, or with presentation (41%), 13 students in interval 41-60 with category is enough, or with presentation (33%), and 4 students in interval 21-40 with category is poor, or with presentation (10%)and 0 students in interval 00-40 with category is Very poor, or with presentation (0%). In conclusion, the overall students' ability in using the picture was good.